(untitled) (Journal of Engineering, 2024)
Traffic congestion become a serious problem that traffic engineers still face. This research explains the sustainable indicators and congestion index for urban streets and their implementation to evaluate the performance measures proceeding toward sustainable roads. Congestion measures in terms of speed reduction and sustainable indicators; mobility (congestion index, travel time, and delay), costs (vehicle operating cost), socio-economic effect (in terms of an estimated factor called User Satisfaction Index (USI), and air pollution (Fuel emissions) are estimated. Link 3 has the highest delay value of approximately (2 minutes) for the evening peak period in the north-south direction due to a large number of vehicles dense traffic and mixed land use of the study area that produce many attraction trips daily. Congestion is distributed more spatially during the morning peak periods, while in evening periods is relatively concentrated on a specific link. The reduction in travel speed due to the congestion effect induced higher vehicle operating costs of an average unit of 2.9 per Km for links 1, 2.6, and 2.4 for links 2 and 3, respectively, at peak time from (8 a.m. to 12 a.m.). Generally, traffic congestion is mainly concentrated on Links 1 and 3 of Palestine’s urban street segments. The overall user satisfaction index (USI) is 2.209 and about 44.18%, meaning user satisfaction is less than 50%. This illustrates that the selected segment of the study area is unsustainable regarding the social and commuter opinions aspect.